Global, regional, and national burden of hearing loss from 1990 to 2021: findings from the 2021 global burden of disease study - Ying Shen; Tianjiao Zhou; Wentao Zou; Jiaxiong Zhang; Shuwen Yan; Haibo Ye; Weijun Huang (Annals of Medicine, 2025)
Background Hearing loss is a global health issue affecting millions and imposing a significant burden. This study aimed to retrospectively and predictively assess the prevalence and years lived with disability (YLDs) due to hearing loss, stratified by sociodemographic index (SDI), age, and sex.Methods Data from the 2021 Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) were used to analyze the prevalence and YLD burden of hearing loss across different subgroups. Age-standardized prevalence rates (ASPR), age-standardized YLD rates (ASYR), and estimated annual percentage changes (EAPCs) were calculated to assess trends.Results In 2021, over 1.5 billion individuals had hearing loss, resulting in significant disability burden. EAPCs for ASPR and ASYR from 1990 to 2021 were 0.16 (95% confidence intervals [CI]: 0.15-0.17) and 0.17 (0.16-0.18) respectively. Regions with middle SDI had the highest prevalence, ASPR, YLDs, and ASYR, while high SDI regions had the lowest. ASYR and ASPR were negatively correlated with SDI across regions in most regions. Males had significantly higher ASPR and ASYR than females. ASPR and ASYR increased with age. Projections from 2022 to 2050 indicated a continued rise in ASPR, with a slight decline in ASYR.Conclusions Hearing loss burden increased from 1990 to 2021, with notable differences across regions, genders, and age groups. High SDI areas had the lowest burden, while middle SDI regions experienced the most severe hearing loss. Low SDI areas had a higher disability ratio relative to prevalence. Males and older adults bore a disproportionately high burden of hearing loss.